Descarte racional de componentes eletrônicos com geração de insumos, subprodutos e produtos: manual de referência técnica - GOMES, Freud Antonio Martinelli (2015)
In all sectors of modern society there is an increasing use of electronic equipment. The humankind makes use of these equipment in all activities: work, leisure, safety, communication, education and politics. Technological evolution continuously provides new models of electronic equipment, with more features, better economy rates and higher value. On a daily basis new equipment are released and customers are induced to discard old products, making them outdated in spite of their good conditions. As time passes the amount of unused electronic equipment considerably increases in all sectors of society. This scenario contributes to the disposal of obsolete and/or damaged equipment, denominated electronic waste, which, in its way, significantly enhances environmental pollution. A great number of equipment are simply discarded as general waste, regardless some crucial aspects, such as the suitability of the disposal area, or the presence of toxic and/or radioactive components in each equipment. A massive number of out-of-date electronic equipment are commercialised as just scrap metal every day. Thus, there are needed actions aimed to diminish this problem, which is the reason of this work presentation. Considering the above exposed, the objective of this project is to provide a rational disposal of components present in discarded electronic equipment, focusing on the generation of supplies, sub products and products. In order to achieve this objective, the creation of a Technical Reference Manual that defines in a clear, precise and exact way all procedures is needed. Information regarding the disposal of electronic equipment of a public institution will be analysed and, being identified its characteristics and composition, there will be proposed, in the form of a Technical Reference Manual, suitable behaviours with the application of the called ‘reverse logistics’, allowing the rational discard of non-reusable components as well as the generation of inputs, sub products and products derivatives thereof. As a result, it is expected the creation of a Technical Reference Manual to be used as a working tool by other researchers in this field.